Analisis Perbandingan Penggunaan Norma Penghitungan Penghasilan Neto (NPPN) dengan Menyelenggarakan Pembukuan pada Wajib Pajak Orang Pribadi Pekerjaan Bebas - Rieska Aprilia; Ni Luh Gede Erni Sulindawati (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aims to determine what factors influence the auditors at KAP Arthawan, Edward as the Free Work Individual Taxpayer prefers to use the norm method of calculating net income rather than keeping books. This study uses a qualitative method. The results show that the factors that influence auditor taxpayers prefer to use the NPPN method instead of keeping bookkeeping because the calculation process is more practical, easy, fast and efficient because the tax burden that must be paid is much less than the NPPN method. The difference that exists when using the NPPN method and bookkeeping is that those who are obliged to organize are corporate taxpayers and private taxpayers who carry out business activities or independent work, while those who are obliged to organize NPPN are individual taxpayers who carry out business activities or independent work with circulation. gross in one year less than 4.8 billion rupiah and individual taxpayers who do not carry out business activities or independent employment. So it can be concluded that the bookkeeping method is more efficient than NPPN, it is better if individual taxpayers who work as auditors make bookkeeping in their tax calculations and reporting.